Developments of monetary theory in the Netherlands - Jong, Frits J. de. (Rotterdam : Universitaire Pers Rotterdam, 1973)
This book is aimed at exposing English speaking readers to some of the developments of monetary theory published by Dutch authors, written partly in Dutch, German and French. It also present a survey of the work done in monetary analysis, monetary equilibrium, the velocity of circulation of money and its relation with monetary equilibrium.
Includes index
Bibliography: p. 158-163.
usc 24/08/18
Loans
Keywords: Money; Money--Mathematical models; Circular velocity of money; Netherlands